GastroHealth Mission Health Education: A Healthy Digestion Initiative for Active Adolescents - Hartanti, Yesiska Kristina Kristina; Pramitaningastuti, Anastasia S.; Salsabillah, Cecilya Anastasya; Margawang, Audrey Angeline; Nengy, Jefanya; Nadya, Febry; Elvira, Yuyuvia (Universitas Padjadjaran, 2025)
Digestive health issues such as dyspepsia and gastroenteritis are commonly experienced by teenagers due to unhealthy eating habits and poor hygiene practices. The GastroHealth Mission aims to enhance students' knowledge of the prevention and management of digestive disorders through educational and practical approaches. This initiative took place on Friday, November 1, 2024, at a high school in South Tangerang. The methods used included interactive lectures, group discussions, and a hands-on healthy food-making activity under the theme “Wrap It Healthy, Digest It Right!” Evaluation was conducted using pre-tests and post-tests, which were analyzed with an Excel paired t-test to measure knowledge improvement, along with satisfaction questionnaires to assess the effectiveness of the program. The results showed that the average knowledge score increased from 81.18% to 96.67% (an improvement of 19.17%) with a p-value of 0.000, indicating a statistically significant difference before and after the session. Active participation reached 100% (exceeding the 50% target), and participant satisfaction was 92% (surpassing the 80% target). Although the number of participants only reached 72% of the target, students' understanding of the importance of a healthy lifestyle in preventing digestive disorders improved significantly. To maximize the educational impact, similar initiatives should be scheduled earlier to avoid conflicts with other school activities and should involve a larger number of participants with an extended duration for more in-depth material coverage.Keywords: Dyspepsia, gastroenteritis, health outreach, healthy eating habits.